Milk production and milk composition of the Boutsko bred of ewes in Epirus - FOLINAS (Γ. Σ. ΦΩΛΙΝΑΣ) S. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
A flock of 244 hill sheep of the indigenous Boutsko breed of Epirus (NW of Greece), 1-6 years old, reared under a transhumance system was used to study their milk productivity for a period of 14 months (March - June of next year). In addition three groups of ewes, aged 3 to 4 years (group A with 10 ewes suckling a single male lamb, group Βwith 10 ewes suckling a single female lamb and group C with 10 ewes suckling twin lambs) were kept under the same conditions of nutrition and management with the rest of the above flock. They were studied for a 26-week lactation period (4-week suckling period. 22-week milking period) to assess the effect of sex and number of lambs suckled on milk yield, milk composition and body reserves. The results of the study have been summarized as follows: 1) Lactation period (suckling period=4 weeks, milking period=32 weeks) was very long (36 weeks). Throughout milking period milk production of the ewes was 93.7 Kg. Of this 82.3% was produced during the winter period and 17.7% during the summer period. Persistency of milk production was low. One month after weaning of lambs the milk yield of ewes was reduced by 49% and 44% of the level at weaning for singlesuckled and twin-suckled ewes, respectively. 2) Throughout lactation, milk yield and milk composition were not affected by sex of lambs suckled. However, milk yield of ewes was affected by the number of suckled lambs; twin-suckled ewes produced more milk during the suckling period ( + 15.7%, Ρ < 0.05) and milking period (+21.8%, Ρ < 0.05) than those of single-suckled ewes. Fat, protein and dry matter concentration of milk was lower (P<0.05) in twin-suckled ewes than in single-suckled ewes. Concentration of all milk constituents was affected by stage of lactation (P<0.05).